Kebebasan Dan Belenggu: Merinci Perspektif Paulus Tentang Perbudakan Dalam Awal Kekristenan - Cindy Natalia Salinding (Jurnal Magistra, 2024)
This article examines Paul's perspective on slavery in early Christianity with a focus on the concept of spiritual equality and views on spiritual freedom. Although Paul did not explicitly call for the physical liberation of slaves, the concept of spiritual equality in Christ became a moral basis that highlighted the dignity of every individual regardless of social status. Paul's view of spiritual freedom was interpreted as a potential encouragement to support physical and social liberation, although it did not propose direct changes in law or policy. This research also details possible responses of early Christian communities to this concept in practical contexts, including efforts to support human rights and create an ethical environment that respects the values ​​of freedom and human dignity.